Relation of bacteria to disease with tuberculosis as a type - Coe, Maude Mildred (My University, 1902)
Introduction: The scientific study of bacteria may be said to have originated as early as the latter part of the seventeenth century but until recent years the progress in this branch of science has been exceedingly limited which is probably due in a certain degree to the minuteness of the micro-organism with which one must deal in order to make any further discoveries. Bacteria as well as animals may be divided into different races and species and just as the progeny of a certain species of animals under varying conditions tend to become different, so do the descendants of one bacterial species differ. Hence, bacteria do not grow equally well on every culture media or do not always find the body of the same animal always equally suitable. This becomes much more noticeable when bacteria are grown on artificial culture media, for many bacteria are very sensitive to slight chemical changes and also variations in temperature.
Citation: Coe, Maude Mildred. Relation of bacteria to disease with tuberculosis as a type. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Bacteria; Culture; Bacteriology; Theses; Manuscripts (documents)